ANALYSIS OF THE RECURRENCE OF STROKE: A CROSS-SECTIONAL STUDY IN THE UNIVERSITY OF MUHAMMADIYAH MALANG HOSPITAL: RECURRENCE OF STROKE - Lilis Setyowati; Nur Aini; Ollyvia Freeska Dwi Marta; Erma Wahyu Mashfufa; Aditya Anggriawan (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: a recurrence of stroke, is a matter of concern because it can worsen the situation, increase the treatment costs, and increase death risk. Stroke recurrence caused by multifactorial cases. The objective of this study is to analyze the factors associated with stroke recurrence in the university of muhammadiyah malang hospital. Methods: This study  used a cross-sectional observation analytic study. A total sample of 64 people was collected using the purposive sampling technique. The dependent variable in this study was stroke recurrence. The independent variables were the factors that cause stroke recurrence (family history of the disease, comorbidities, physical activity, stress, and knowledge). This study  used the Global Physical Activity Questionnaire(GPAQ), the International Stress Management Association(ISMA), and socio-demographic questionnaire to collect the data. The data were analyzed using the Chi-Square test. Results: a total of 47 patients (73.43%) had stroke recurrence, the majority of the second recurrence. Most types of stroke were ischemic stroke (81.25%). The risk factor significantly associated with stroke recurrence was hypertension (sig 0.026 <0.05). Conclusion: Uncontrolled hypertension increases the process of atherosclerosis that can lead to bleeding and brain infarction.